Rape Culture in Indonesia - Haryati S Slamet; Eti Setiawati; Siti Kholifah (Sekolah Pascasarjana Universitas Brawijaya, 2022)
In Indonesia, most people still adhere to a patriarchal system that allows the practice of violence against women to exist and be understood, even preserved, and become the foundation for the formation of rape culture. Because the root of rape culture is a patriarchal culture where the meeting point lies in the assumption that men are higher than women so that men have special rights over women. Although the culture of rape does not only talk about violence against women but also men, women are the most harmed and victims of this culture. This study aims to provide an overview of the rape culture in Indonesia that occurs in women. The method used in this research is qualitative and uses a literature review as data collection and analysis based on studies from various separate studies on recognizable forms of rape culture. The results show that rape culture in Indonesia still exists today. This is known from the results of an analysis of forms of rape culture, such as the persistence of patriarchal ideology in Indonesia, victim-blaming, sexist behavior, belittling cases of sexual harassment, and belief in rape myths. Keywords: rape culture, sexual violent, women